PENGARUH UKURAN PERUSAHAAN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBAGAN SUB SEKTOR MINYAK DAN GAS BUMI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aulia, Yusuf; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of company size and debt policy on firm value in the oil and gas sub-sector mining company listed on the Indonesia Stock Exchange (IDX). The method used to measure Company Size as an independent variable is Ln Total Assets and Ln Total sales, while the method used in measuring Debt Policy as an independent variable is Debt to Asset Ratio (DAR). The ratio used to measure Company Value as the dependent variable is Price Book Value (PBV). The method used to observe the effect of Company Size and Debt Policy on Firm Value is to use simple linear regression.The data used in this study are secondary data, namely financial statements and annual reports. The data are listed on the Indonesia Stock Exchange (IDX) for 6 years from the period 2012 to 2017. Sampling was carried out by census method, 7 companies were used. Data analysis using simple linear regression analysis and t test. Data analysis uses several linear regression analysis with SPSS 24.The results of the analysis show that the firm size variable has a significant effect on the value of the company in the oil and gas sub-sector mining companies listed on the Indonesia Stock Exchange, and the analysis results show that the debt policy variable does not significantly influence the company's value in the oil and gas subsector earth listed on the Indonesia Stock Exchange. Keywords: Company Size, Debt Policy, Company Value